2001
DOI: 10.1310/7ukk-hj0f-gdwf-hhm8
|View full text |Cite
|
Sign up to set email alerts
|

The Lighthouse Strategy: Improving the Functional Status of Patients with Unilateral Neglect After Stroke and Brain Injury Using a Visual Imagery Intervention

Abstract: This study extends the work of J. Niemeier (1998) by using visual imagery for amelioration of the devastating impact of visual inattention or neglect on recovery from stroke or other brain injuries. Ten individuals with unilateral visual neglect who were undergoing acute physical rehabilitation after brain injury were cued by their interdisciplinary treatment team members to "be like" horizon-illuminating lighthouses and turn their heads left and right during functional and therapy training tasks. These treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 32 publications
0
14
0
1
Order By: Relevance
“…Studies have shown that one strategy to improve task efficiency of people with visual neglect is to cue them in using a light house visual imagery strategy while performing functional tasks. (17,18) A horizon illuminating light house typically has a light at its top that sweeps left to right to guide ships at sea to safety. The light house visual imagery strategy encourages users to scan the environment around them by turning their heads as and when required.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that one strategy to improve task efficiency of people with visual neglect is to cue them in using a light house visual imagery strategy while performing functional tasks. (17,18) A horizon illuminating light house typically has a light at its top that sweeps left to right to guide ships at sea to safety. The light house visual imagery strategy encourages users to scan the environment around them by turning their heads as and when required.…”
Section: Methodsmentioning
confidence: 99%
“…Patients are instructed to start scanning from the anchor cue. In one study, this strategy was internalized by teaching the patient to turn his head until the tip of his chin was in line with the top of his left shoulder and to move his head until the tip of his chin was in line with the top of his right shoulder (51).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, little change in cognitive deficits is expected in cognitive strategy training (2). However, the 13 studies we included in our review did evaluate transfer effects of strategy training to neuropsychological test results in addition to one of the other types of transfer we distinguished (22,23,26,27,29,31,34,36,47,48,(50)(51)(52). Eleven studies did report transfer to neuropsychological test results.…”
Section: Choice Of Outcome Measuresmentioning
confidence: 99%
“…Other spatial neglect treatment approaches are available and used in the USA, but most of these also utilize top-down (goal-driven) strategies to enrich visual perception and monitoring, and are intended for self-implementation. These strategies include training of visual awareness, 22 therapist-coached use of mental imagery (the ‘lighthouse strategy’ 23 ), and review with a therapist of videotaped feedback of task performance. 24 …”
Section: Current Therapeutic Approachesmentioning
confidence: 99%